Evolution Trend and Cause Analysis of Diversion Characteristics of Three Outlets Along Jingjiang River Under New Flow and Sediment Conditions - Wang, Dong; Zhou, Tao; Fan, Jiaze; Tang, Zhengyang; Wang, Yongqiang (Sustainability, 2025)
Changes in the diversion characteristics of three outlets along Jingjiang River are of vital importance to the adjustment of river–lake relationships. This study analyzed the mechanism of periodic changes in the diversion ratio of the three outlets along the Jingjiang River after the storage of the Three Gorges Reservoir. It used the latest measured flow and sediment data. The analysis was conducted from the perspective of changes in the main stream regime at the three outlets along the Jingjiang River and the erosion and deposition trend of the floodway at the three outlets. On such a basis, the contribution ratio of three factors was analyzed quantitatively. These factors are Jingjiang River runoff reduction, reservoir regulation action, and diversion capacity drop. This analysis comprehensively considered the diversion capacity of the floodway at three outlets. It also considered the annual runoff volume and runoff process of the Jingjiang River mainstream. The purpose was to reveal the change laws of water resource quantity and response mechanism of Dongting Lake area under the new flow and sediment conditions. This will provide technical support for the sustainable management of water resources in the basin and the adaptive operation of reservoirs. The analysis results indicated that the diversion volume reduction at the three outlets along Jingjiang River is jointly caused by the regulation of the Three Gorges Reservoir and the runoff volume of the incoming flows of Jingjiang River. Seen from the proportion, the reservoir regulation action takes up 35% before the Three Gorges Reservoir is filled to 175 m, and less runoff of Jingjiang River takes up 65%; after the reservoir runs normally when filled to 175 m, the reservoir regulation action takes up 63%, the proportion of the diversion capacity drop of the three outlets causing diversion volume reduction takes up 2.5%, and less runoff of Jingjiang River takes up 34.5%.